2012
DOI: 10.5053/ekoloji.2012.834
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Species Composition and Abundance in the Southwestern Caspian Sea

Abstract: This study, accomplished is focused on the spatial and temporal distribution and species composition of phytoplankton in the southwestern Caspian Sea between January 2008 and December 2008. Samples were collected from 11 stations along three transects known as Lisar, Anzali and Sefidrood. This study identified 43 phytoplankton species comprised of diatoms (25 species), dinoflagellates (7 species), chlorophytes (6 species), cyanophytes (4 species), and euglenoids (1 species) were identified. The study showed, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
2
14
0
1
Order By: Relevance
“…Considering contributions of different taxonomic groups to the total phytoplankton cell density, diatoms were still an important group both qualitatively and quantitatively in the south western Caspian Sea in the study period (Figure 3). Similar to previous studies in the Caspian Sea (Nasrollahzade et al, 2008a, 2008bBagheri et al, 2011Bagheri et al, , 2012bBagheri et al, , 2012c, this study showed that diatom communities were represented by a few dominant species such as D. fragilissimus and T. nitzschioides in the system. However, it is known that as aquatic systems are polluted by excessive anthropogenic nutrient inputs by rivers or other discharges such as domestic waste waters, qualitative and quantitative exchanges between different taxonomic groups of phytoplankton will generally be broken down against to the diatoms (Turkoglu and Koray, 2000Turkoglu, 2005; Table 5.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Considering contributions of different taxonomic groups to the total phytoplankton cell density, diatoms were still an important group both qualitatively and quantitatively in the south western Caspian Sea in the study period (Figure 3). Similar to previous studies in the Caspian Sea (Nasrollahzade et al, 2008a, 2008bBagheri et al, 2011Bagheri et al, , 2012bBagheri et al, , 2012c, this study showed that diatom communities were represented by a few dominant species such as D. fragilissimus and T. nitzschioides in the system. However, it is known that as aquatic systems are polluted by excessive anthropogenic nutrient inputs by rivers or other discharges such as domestic waste waters, qualitative and quantitative exchanges between different taxonomic groups of phytoplankton will generally be broken down against to the diatoms (Turkoglu and Koray, 2000Turkoglu, 2005; Table 5.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Sharifi (2006) noted that the monthly average precipitation amounts exceeded monthly average evaporation levels in the south western Caspian Sea. Reverse to the annual findings in temperature, the salinity values during the study were more similar to the previous findings (Dumont, 1998;Kideys and Moghim, 2003;Roohi et al, 2010;Hosseini, 2011;Bagheri et al, 2012bBagheri et al, , 2012c.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rodionov [21], Bilio and Niermann [22], and Polonskii et al [23] theorized that hydrobiological changes in the Caspian Sea, Black Sea, and Baltic Sea during the 1990s and 2000s could de�nitely be correlated to these changes. Recent remarks on other seas indicated that the shiing plankton communities can also be related to climatic inconsistency [7,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Selain klorofil-a, terdapat pula klorofil-b, klorofil-c, dan pigmen-pigmen pelengkap lainnya yang ditemukan pada beberapa jenis organisme yang berfotosintesis. Klorofil-a dan klorofil-c ini dapat memberi sumbangsih indikator pertumbuhan dinoflagellate, seperti jenis Protoceratium reticulatum (Bagheri et al, 2012). Klorofil-a dan klorofil-c menunjukkan peningkatan pertumbuhan dinoflagellate (Protoceratium reticulatum) seiring dengan peningkatan kandungan unsur hara, seperti nitrat dan fosfat yang tinggi serta penyinaran sinar matahari yang cukup (Ratti et al, 2011).…”
Section: Pendahuluanunclassified